Analysis of Entrepreneurial Potential in the Maritime Sector (Case Studi on Politeknik Maritim AMI Makassar) - Irman Irman; Hardiyono (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to identify the entrepreneurial potential among the cadets of the AMI Makassar Maritime Polytechnic and the factors that affect their interest in the maritime sector. Based on in-depth interviews, participatory observations, and documentation, it was found that the interest in entrepreneurship among cadets is still low. The main reasons include a preference for job security as an employee, a lack of understanding of maritime business opportunities, and a lack of support from the environment. This research identifies various business opportunities in the maritime sector such as fisheries business, logistics, marine tourism, and marine energy. Factors that affect entrepreneurial interest include self-motivation, family support, access to capital, and educational curriculum. To increase interest in entrepreneurship, it is recommended to strengthen the entrepreneurship curriculum, develop mentorship programs, increase access to capital and business networks, and support the environment. The results of this research are expected to provide insight for educational institutions and the government in designing effective strategies to support the development of entrepreneurship in the maritime sector, so that it can support sustainable national economic development.